ChemInform Abstract: Catalytic Diastereo‐ and Enantioselective Annulations Between Transient Nitrosoalkenes and Indoles. Issue 20 (25th April 2013) - Zhang, Yu; Stephens, David; Hernandez, Graciela; Mendoza, Rosalinda; Larionov, Oleg V.
Abstract For the first time a highly enantioselective catalytic [4+2] annulation of unstable and extremely reactive in situ prepared nitrosoalkenes is developed by using the synergistic combination of copper catalyst and a silver base.